El derecho a la impugnación del procesado: Análisis del Art. 653 del Código Orgánico Integral Penal - Rodríguez Gaona, Josselyn Magaly (2024)
The problem identified in this research is the impossibility of appealing the order to call for trial according to Article 653 of the Comprehensive Organic Criminal Code (COIP), which generates a violation of the guarantees of challenge, equality and non- discrimination. The main objective was to analyze theoretically, legally and doctrinally this violation, exploring the implications of the lack of an appeal on procedural fairness. The methodology employed was a mixed approach, using both empirical and descriptive methods to collect and analyze qualitative and quantitative data. The results show that the impossibility of appealing this order negatively affects procedural equality, the presumption of innocence and the right to an effective defense. The research concludes that a reform of article 653 of the COIP is necessary to include the possibility of appealing the order to call for trial, thus guaranteeing a more equitable judicial system that respects the fundamental rights of the accused.